2020
DOI: 10.1093/ptj/pzaa099
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapist Management of Total Knee Arthroplasty

Abstract: A clinical practice guideline on total knee arthroplasty was developed by an American Physical Therapy (APTA) volunteer guideline development group that consisted of physical therapists, an orthopedic surgeon, a nurse, and a consumer. The guideline was based on systematic reviews of current scientific and clinical information and accepted approaches to management of total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 120 publications
1
88
0
Order By: Relevance
“… 41 , 42 The American Physical Therapy Association identified the need for research to investigate the optimal timing of post-TKR rehabilitation. 43 Our findings suggest that initiating outpatient PT care within 30 days after TKR may be associated with a lower risk of long-term opioid use.…”
Section: Discussionmentioning
confidence: 60%
“… 41 , 42 The American Physical Therapy Association identified the need for research to investigate the optimal timing of post-TKR rehabilitation. 43 Our findings suggest that initiating outpatient PT care within 30 days after TKR may be associated with a lower risk of long-term opioid use.…”
Section: Discussionmentioning
confidence: 60%
“…Many treatments exist for OA, and major guidelines have recently been published providing recommendations for their usage (29)(30)(31). Most currently available treatments primarily target symptom management as opposed to disease pathobiology.…”
Section: Oa Treatmentsmentioning
confidence: 99%
“…Most currently available treatments primarily target symptom management as opposed to disease pathobiology. There are currently no therapeutic agents that reverse or halt OA progression, resulting in continued disease progression in millions of patients with OA (30)(31)(32). A summary of the treatments covered in this review can be found in Table 1.…”
Section: Oa Treatmentsmentioning
confidence: 99%
“…The use of these sensor systems holds the potential to measure knee metrics during activities of daily living as well as to track and guide patients’ home exercise physiotherapy program during recovery. However, accurate measurement of the knee flexion angle by these skin-mounted sensors is essential to achieve the above goals [ 7 ].…”
Section: Introductionmentioning
confidence: 99%